Analysis of Hoax News Content in the 2024 Presidential Candidate Election on Facebook Account Kompas.com - Andiva, Krista; Nurdiarti, Rosalia Prismarini; Saputri, Dhea Octavia (PT FORMOSA CENDEKIA GLOBAL, 2025)
The research is aimed at finding out the objectivity of Pilpres 2024 hoax announcement on the Facebook account Kompas.com. The theory used in this study is the theory of media objectivity. This research is a quantitative research using news content analysts. The object of this research is hoax announcement in the election of 2024 presidential candidates on the Facebook account Kompas.Com. Analysis of research data using content analysis techniques. The results of the research published on Facebook Kompas.com are by considering the aspects of the message as investigated in this study that are the dimensions of truth, relevance,balance and neutrality. The results of the research show that on the unit of analysis is the explaining factuality associated with the accuracy assessment that is more dominant than the overall news. The social media hoax in the election of apresidential candidate does not completely influence the reader in determining his choice, he will understand the event based on the information he has received with his experience, in this case his experience can be gained by analyzing the event on the basis of other sources that are more reliable.